Framework for the Circumpolar Expansion of the Local Environment Observer Network - Arctic Contaminants Action Program (ACAP) (Arctic Council Secretariat, 2017)
Climate change is impacting the Arctic at a significant rate. Arctic communities experience first-hand the challenges of a rapidly changing environment in remote locations across the circumpolar north. Community-based monitoring networks in rural communities can help connect indigenous, traditional, local, and ecological knowledge with scientists, policymakers and technical experts, creating trust, developing collaborative approaches, and solutions to human health and environmental problems resulting from contaminants and pollution. Under the U.S. Chairmanship of the Arctic Council, partners in the ACAP Working Group and its subsidiary Indigenous Peoples Contaminants Action Programme (IPCAP), are building on the success of the Alaska Native Tribal Health Consortium's (ANTHC) Local Environmental Observers (LEO) network in Alaska and developing the foundation for a Circumpolar Local Environmental Observer (CLEO) Network.